Analysis Of Lead Levels (Pb) In Public Transport Drivers’hairbyusing Automic Absorption Spectrophotometer (AAS) Method - Wini Alimudin; Sulfiani Sulfiani; Julia F. N (Poltekkes Kemenkes Pakassar, 2021)
Lead levels (Pb) is a heavy metal that is toxic to humans. There are many people do their activites on the highway, one of them is a public transport driver. Public transport driversare works who have a considerable by using an Atomic Absorption Spectrophotometer (AAS). The aim of research was todetermine the levels of lead (Pb) in the hair of public transport driver. The number of samples was 11 respondents of public transport drivers by using accidental sampling technique. Based on the research results found that the concentration of heavy metal lead (Pb) in hair of public transport drivers. The results shows that sample code (A) with thelength of working was 20 years, the Pb level : 65.10 µg/g; sample (B) with thelength of working was 30 years, Pb level : 91.44 µg/g; sample (C) with thelength of working was 15 years, Pb level : 39.11 µg/g; sample (D) with thelength of working was 14 years, Pb level : 39.37 µg/g; sample (E) with thelength of working was 3 years, Pb level : 12.20 µg/g; sample (F)with thelength of working was 7 years Pb level : 30.26 µg/g; sample (G) with thelength of working was 9 years Pb level : 15.90 µg/g; sample (H) with thelenght working was 15 years Pb level : 40.98 µg/g; sample (I) with thelenght working was 10 years Pb level : 74.55 µg/g; sample (J) with thelenght working was 10 years, Pb level : 36.50 µg/g; sample (K) with thelenght working was 6 years, Pb level : 18.60 µg/g. It can be concluded that the lead levels (Pb) in all research samples have Pb levels exceeding the threshold value, where the maximum tolerance limit for lead levels in hair based on WHO is ≤ 12 µg/g.